Family-School Partnership Counselling for Student Educational Resilience: Islamic Perspectives and the Sustainable Development Goals - Hidayat Hidayat; Indah Aminatuz Zuhriyah; Anik Niswatul Karimah; Ruli Astuti; Kususanto Ditto Prihadi (AL-ISHLAH: Jurnal Pendidikan, 2025)
The educational resilience of students in rural madrasahs, particularly within vulnerable socio-economic contexts, is a strategic concern that requires a collaborative and value-driven framework. This study addresses the need for a contextual model that integrates Islamic values to support student development. A descriptive qualitative method was employed to explore the dynamics of an educational partnership among families, schools, psychosocial support systems, and communities. Data were collected through in-depth interviews, participatory observations, and documentation involving key stakeholders, including guidance and counseling (BK) teachers, madrasah principals, parents, students, and community leaders at MAS Nurul Islam Bades Pasirian, Lumajang. Findings reveal that madrasahs serve as socio-religious mediators, aligning the roles of schools, families, and communities through Islamic values such as amanah (trustworthiness), justice, and deliberation. BK teachers provide counseling grounded in empathy, patience, and sincerity, while community support is reflected in the distribution of zakat, infak, and various social solidarity programs. The proposed Family–School–Psychosocial–Community (FSPC) model fosters student resilience by embedding a participatory and transcendental approach into educational practices. The FSPC model proves structurally and spiritually effective in enhancing students’ educational resilience. It underscores the importance of incorporating Islamic values into madrasah partnership policies and calls for strengthening BK teachers’ capacity through training rooted in Islamic spirituality.